'Forgiveness' in Building Bridges With Muslims: An Intertextual Analysis of the Joseph's Narrative. (April 2023) - Hyun, Hanna
Joseph's story in Genesis 37–50 is well-known among Christians. It is similar to the Torah's account of Yōsef's life. The Islamic version celebrates the triumph of the virtuous. In contrast, the biblical narrative highlights the unwavering loyalty of Joseph to his family and forgiveness; an account that could serve as a model for coexistence and fostering harmonious interfaith relations. In this article, the Qurʾānic story of al-Yῡsuf, as well as the Jewish and Christian interpretations of the same story, are used for an intertextual interpretation. Drawing from the idea of 'from the foreign to the familiar, ' the author describes Joseph's story in Islamic, Jewish and Christian traditions in that sequence. Joseph's story, she suggests, has valuable lessons for the Jews, Christians and Muslims who are connected with each other in a sense through this common narrative; she argues that an intertextual reading of similar narratives in their traditional sources has promise for building bridges between them.